Tantangan Dan Implementasi Pengembangan Kurikulum Pendidikan Agama Islam - Dudung Abdul Rahman (Sekolah Tinggi Ilmu Tarbiyah Tihamah, 2023)
Islamic religious education is still at the understanding process stage, not yet fully at the application stage. This study adopted a qualitative descriptive analysis method. The approach used in this study is the library research approach. the teacher is a